2021
DOI: 10.1016/j.atmosenv.2020.118132
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional variations in aerosol loading during COVID-19 imposed lockdown

Abstract: In the backdrop of upward trend in anthropogenic aerosols over global hotspot regions, the air quality had improved worldwide post declaration of the Corona virus disease-2019 (COVID-19) as a global pandemic in mid-March-2020. Present study using Moderate Resolution Imaging Spectroradiometer (MODIS) satellite derived aerosol optical depth (AOD) and the Modern-Era Retrospective analysis for Research and Applications (MERRA) version-2 datasets however, demonstrated the regional variation in aerosol loading durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 33 publications
5
30
0
Order By: Relevance
“…Overall, the monthly deviation of AOD (at different wavelengths) during the lockdown period ranges between ~ 25-50% for Kyanjin_Gompa and ~ 20-60% for Pokhara, with a maximum decrement of AOD in the month of March. This result is consistent with the global study of AOD during the lockdown period by Sanap [23]. However, comparatively less deviation in AOD was observed in the month of April and May.…”
Section: Diurnal Variation Of Mean Aodsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, the monthly deviation of AOD (at different wavelengths) during the lockdown period ranges between ~ 25-50% for Kyanjin_Gompa and ~ 20-60% for Pokhara, with a maximum decrement of AOD in the month of March. This result is consistent with the global study of AOD during the lockdown period by Sanap [23]. However, comparatively less deviation in AOD was observed in the month of April and May.…”
Section: Diurnal Variation Of Mean Aodsupporting
confidence: 91%
“…Raza et al [22] reported that AOD was reduced in Pakistan during the lockdown period in 2020 in comparison to the previous years. From the worldwide study of AOD during the pandemic period, Sanap [23] recorded a decrease in AOD from mid-March to April 2020; however, a drastic reduction in AOD was observed in May. Furthermore, despite many impacts of lockdown on people's social life and the national economy, several ndings [e.g., Shrestha et al [24], Gautam et al [25], Baral & Thapa [26] observed that lockdown had temporarily better environmental conditions in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…The lockdown measures had a pronounced effect on social life and on industry and commerce. This led to a reduction in motorized traffic and thus supposedly [14] also to measurable reductions in traffic-related air pollutants, namely NO2. We observed a relatively quick change in the behavior as the measures were announced on Friday and went into force on Monday.…”
Section: Methodsmentioning
confidence: 99%
“…The data obtained provided by the daily fire mask compounds derived from MODIS radiances show the presence of active fires in rural areas of the countries of Colombia and Venezuela. Sanap (2021) estimated global and regional variations in aerosol loading imposed by the lockdown. Their results show that, in northern Colombia where our study area is located, forest fire emissions contributed significantly to the high aerosol and associated negative aerosol radiative forcing anomalies during the April lockdown.…”
Section: Accepted Manuscriptmentioning
confidence: 99%